Ethnic Behavior and Lifestyle of the Togutil Tribe in East Halmahera Regency, North Maluku - Bahrudin Hasan; Sihabudin Sihabudin; Jamalullail Jamalullail (Peneliti.net, 2021)
The purpose of this study was to find out the communication patterns that occurred between the Tugutil tribe and the local community that led to acculturation in East Halmahera Regency. The research approach used is qualitative research, which seeks to understand, explain and analyze the acculturation process between the Tugutil tribe and other ethnic communities in the